Fast detection technique for voltage unbalance in three-phase power system - Ibrahim I. Al-Naimi; Jasim A. Ghaeb; Mohammed J. Baniyounis; Mustafa Al-Khawaldeh (Institute of Advanced Engineering and Science, 2021)
In this paper, the problem of voltage unbalance in the three-phase power systems is examined. A fast detection technique (FDT) is proposed to detect the voltage unbalance precisely and speedily. The well-known detection methods require more than one cycle time to detect the unbalanced voltages, whereas the proposed technique detects the unbalanced situations speedily in a discrete manner. Reducing the time duration required to detect the unbalanced voltages will enhance the dynamic response of the control system used to balance these voltages. The FDT acquires the instantaneous values of the three load voltages, calculates the sum and the space vector for these voltages at each sample, and utilizes these parameters to detect the voltage unbalance accurately within a quarter of the cycle time. A proof-of-concept simulation model for a real power system has been built. The parameters of the aqaba-qatrana-south amman (AQSA) Jordanian power system are considered in the simulation model. Also, several test cases have been conducted to test and validate the capabilities of the proposed technique.